Using Yeast in Tomato Production - Atawnah, Waleed; Mansour, Hamza; Ateeq, Mahmoud; Khlaif, Ayman; Zakef, Osama (My University, 2018)
Tomato considered one of the most important vegetables in Palestine, so there is many efforts to improve its yield and properties as producing new cultivares,to improve the surrounding environment and in our case using microorganisms.
Keywords: Yeast,Tomato ,Fertilized.